Conceptual systemigram model: impact of electronic governance on sustainable development. (2016) - Khansari, Nasrin; Finger, Matthias; Mostashari, Ali; Mansouri, Mo
This paper explores the influence of electronic governance (e-governance) on sustainable development. Using a soft systems methodology, it maps the impact of information and communication technologies (ICTs) on the decision-making process. The paper further discusses the role of information technologies as a way for residents to contribute to this decision-making process, and explores the mechanisms by which information sharing can help to overcome bounded rationality problems within urban governance. E-governance mechanisms can increase policy effectiveness, accountability, transparency and ownership within urban systems. The resulting conceptual systemigram model shows how communication and collaboration within an urban system can result in more effective governance structures and practices and the improvement of sustainable development process.